2007
DOI: 10.1016/j.neubiorev.2007.04.002
|View full text |Cite
|
Sign up to set email alerts
|

The behavioral actions of lithium in rodent models: Leads to develop novel therapeutics

Abstract: For nearly as long as lithium has been in clinical use for the treatment of bipolar disorder, depression, and other conditions, investigators have attempted to characterize its effects on behaviors in rodents. Lithium consistently decreases exploratory activity, rearing, aggression, and amphetamine-induced hyperlocomotion; and it increases the sensitivity to pilocarpine-induced seizures, decreases immobility time in the forced swim test, and attenuates reserpine-induced hypolocomotion. Lithium also predictably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
1
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(103 citation statements)
references
References 256 publications
(286 reference statements)
3
96
1
3
Order By: Relevance
“…We confirmed previous studies demonstrating that pretreatment with lithium intraperitoneally (100 mg/kg) 1 h before amphetamine injection in WT mice attenuates amphetamine-induced hyperactivity relative to WT mice pretreated with saline before injection with amphetamine (30 min after amphetamine, F (4,25) ϭ 11.904, Fisher's p ϭ 0.0035) (Fig. 6C) (Takigawa et al, 1994;Frey et al, 2006;O'Donnell and Gould, 2007). The response to amphetamine of VGF ϩ/Ϫ mice pretreated with LiCl was indistinguishable from that of WT mice pretreated with saline, suggesting that LiCl has no effect in VGF ϩ/Ϫ mice (30 min after amphetamine, F (4,25) ϭ 11.904, Fisher's p ϭ 0.9056).…”
Section: Vgf Mimics the Effects Of Licl And Is Required In A Mouse Sysupporting
confidence: 90%
“…We confirmed previous studies demonstrating that pretreatment with lithium intraperitoneally (100 mg/kg) 1 h before amphetamine injection in WT mice attenuates amphetamine-induced hyperactivity relative to WT mice pretreated with saline before injection with amphetamine (30 min after amphetamine, F (4,25) ϭ 11.904, Fisher's p ϭ 0.0035) (Fig. 6C) (Takigawa et al, 1994;Frey et al, 2006;O'Donnell and Gould, 2007). The response to amphetamine of VGF ϩ/Ϫ mice pretreated with LiCl was indistinguishable from that of WT mice pretreated with saline, suggesting that LiCl has no effect in VGF ϩ/Ϫ mice (30 min after amphetamine, F (4,25) ϭ 11.904, Fisher's p ϭ 0.9056).…”
Section: Vgf Mimics the Effects Of Licl And Is Required In A Mouse Sysupporting
confidence: 90%
“…In the present manuscript we do not address the role of AMPA receptors in mediating the effects of lithium in models of manic-like behavior. Available rodent models for the antimanic effects of lithium include attenuation of amphetamine-induced hyperlocomotion and attenuation of aggression (O'Donnell and Gould, 2007), which should be evaluated for the relevance of AMPA receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that TAT-KLCpCDK, a peptide that specifically inhibits the phosphorylation of KLC2, possessed both antidepressantlike and antimanic-like properties in animal models of moodassociated behaviors, thus mimicking lithium's effect on these behaviors. Numerous studies have shown that in addition to its clinical antimanic effects, in animal models lithium has robust antidepressant-like effects in the forced swim and tail suspension tests (30). These antidepressant-like effects can be blocked by the AMPAR inhibitor GYKI52446 (31).…”
Section: Gsk-3 Regulation Of Ampar Trafficking As a Mechanism For Affmentioning
confidence: 99%